Association between preoperative autonomic nervous system function and post-induction hypotension in elderly patients: a protocol for a cohort study. Issue 1 (30th January 2023) - Cui, Quexuan; Che, Lu; Zang, Han; Yu, Jiawen; Xu, Li; Huang, Yuguang
Abstract : Introduction: Post-induction hypotension (PIH), which is prevalent among elderly patients, is associated with adverse perioperative outcomes. As a critical part of blood pressure regulation, baroreflex control is believed to be closely related to intraoperative blood pressure fluctuations. Spontaneous baroreflex sensitivity and heart rate variability measurement can aid evaluation of patients' autonomic function. This study aims to determine the association between preoperative decreased baroreflex function and PIH in elderly patients. Methods and analysis: This prospective cohort study will enrol patients who are 65 years old and above, scheduled for elective non-cardiac surgery under general anaesthesia, and American Society of Anesthesiologists physical status I–III (n=180). Baseline assessment will include routine preoperative evaluations as well as symptoms and anamneses associated with baroreflex failure. Preoperative autonomic function monitoring will be performed through 20 min of continuous beat-to-beat heart rate and blood pressure monitoring using LiDCO rapid (Masimo Corporation, USA). The primary outcome will be PIH. Detailed use of anaesthetic agents during induction and maintenance will be documented for adjustment in multivariable analyses. Ethics and dissemination: The Research Ethics Committee of Peking Union Medical College Hospital approved the study protocol (I-22PJ008). We aim to publish and disseminate our findings in peer-reviewed journals. Trial registration number: NCT05425147 .